Child development - Santrock, John W. (McGraw-Hill Humanities, 2011)
"Thorough. Accurate. Reliable. Engaging. These are just a few of the words used by adopters and reviewers of John Santrock's Child Development. A new Connections theme shows how it all fits together in the the most accurate and up-to-date topically-organized text in the field. Used by hundreds of thousands of students over twelve editions, Santrock's proven learning system provides a clear roadmap to content mastery. The fully revised thirteenth edition continues with Santrock's highly contemporary tone and focus, featuring over 1,000 new citations"--